2022
DOI: 10.1111/nph.18143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals a dynamic genome evolution in the ectomycorrhizal milk‐cap (Lactarius) mushrooms

Abstract: Ectomycorrhizal fungi play a key role in forests by establishing mutualistic symbioses with woody plants. Genome analyses have identified conserved symbiosis-related traits among ectomycorrhizal fungal species, but the molecular mechanisms underlying host specificity remain poorly known.We sequenced and compared the genomes of seven species of milk-cap fungi (Lactarius, Russulales) with contrasting host specificity. We also compared these genomes with those of symbiotic and saprotrophic Russulales species, aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 69 publications
(110 reference statements)
0
22
0
Order By: Relevance
“…The Scaffold N(x) length distribution in L. hatsudake JH5 was also significantly higher than the length of Scaffold N(x) distribution in L. hatsudake MG20 (Figure 2). In total, this L. hatsudake genome assembly represents a significant improvement than that of other previously released Lactarius genomes (contig N50: 5.0 kb-261.3 kb) (Table 1) (Li et al 2020,Saier et al 2014,Lebreton et al 2022). Compared with L. hatsudake 109 genome assembly, JH5 genome show the considerable N50 length (223.2 kb vs 261.3 kb), and BUSCO results (89.0% vs 87.6 % ).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The Scaffold N(x) length distribution in L. hatsudake JH5 was also significantly higher than the length of Scaffold N(x) distribution in L. hatsudake MG20 (Figure 2). In total, this L. hatsudake genome assembly represents a significant improvement than that of other previously released Lactarius genomes (contig N50: 5.0 kb-261.3 kb) (Table 1) (Li et al 2020,Saier et al 2014,Lebreton et al 2022). Compared with L. hatsudake 109 genome assembly, JH5 genome show the considerable N50 length (223.2 kb vs 261.3 kb), and BUSCO results (89.0% vs 87.6 % ).…”
Section: Resultsmentioning
confidence: 88%
“…What is currently known is that, based on whole-genome sequencing, sexual reproduction was found to be heterotypical coordinated in Tuber melanosporum (Martin et al 2010), while Laccaria bicolor was found to possess a family of genes associated with symbiosis, called the “symbiosis toolbox” (Martin et al 2008; Martin and Selosse 2008). Studies have revealed a great diversity of genomic landscapes and gene pools within Russulaceae (Lebreton et al 2022). These results suggest that in-depth analysis of the genomic characteristics of mycorrhizal edible fungi by genome sequencing technology can help to identify and clarify the process of mycorrhiza formation and fruiting body development, thus contributing to an efficient and sustainable cultivation of this edible mycorrhizal fungi.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported taxon-specific expression of small secreted proteins (SSPs) that likely function as effectors in fungus-plant interactions in Suillus , which may explain the association between the host of this fungal taxon and Pinaceae ( Lofgren et al, 2021 ). Even in saffron milk caps, specific SSPs bearing LysM have been reported ( Lebreton et al, 2022 ). The identification of specific SSPs that determine the conifer hosts of T. matsutake and control gene expressions to influence host colonization levels would dramatically facilitate T. matsutake cultivation.…”
Section: Matsutake Cultivationmentioning
confidence: 99%